Исследование неопределенности измерения, связанной с отсчетом по нелинейной шкале. - Захаров, И. П.; Погибко, Р. В.; Волков, О. О. (Харківський університет повітряних сил, 2014)
A measuring uncertainty, associated with nonlinear scale reading is explored. An equation for calculation this uncertainty is proposed.
Exploration of a measuring uncertainty, associated with nonlinear scale reading
Keywords: reading error; nonlinear scale; measuring uncertainty